PENGARUH KUALITAS HUBUNGAN DAN KEMAMPUAN ADAPTASI TERHADAP LINGKUNGAN YANG MEMPENGARUHI KEUNGGULAN BERSAING DAN IMPLIKASINYA PADA KINERJA - Winata, Felix Andhy; J.Sugiyanto, Miyasato (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2016)
The business world is now facing more challenges: limited resources, increasing competition and rapidly changing environment. Demands in the distribution company also added by increasing the amount of principal that shorten the distribution channel. PT. Aga is the official distributor of paint products from PT. A for the Central Java. PT. Aga’s performance who continued to decline during the past two years after the change of management becomes a problem.The aim of this study was to examine the factors that should be improved by PT. Aga to improve itsdistribution performance. This study uses the relationship view as a background theory. Relationship Quality between PT. Aga with its customers, and PT. Aga’s Adaptation Capabilities are factors that will be examined related to competitive advantage and performance.The sample was 200 customers of PT. Aga. 124 questionnaires were analyzed using Structural Equation Modeling (SEM). The analysis shows that the Adaptation Capabilities to the Environment and Relationship Qualityto its customers, have a significant positive influence on performance, either directly or indirectly.PT. Aga should have paid more attention to the Adaptation Abilities, by increasing the communication speed when a change in principal’s policy, and improve the ability to cope with non-routine products / new products, in order to increase their competitive advantage, which ultimately increases its performance.